Acute Variceal Hemorrhage in Germany–A Nationwide Study of 65,357 Hospitalized Cases - Alexander Mertens; Tobias Essing; Anselm Kunstein; Christian Weigel; Johannes Bode; Christoph Roderburg; Tom Luedde; Jennis Kandler; Sven H. Loosen (Canadian Journal of Gastroenterology and Hepatology)
Conclusion: Our study provides detailed insight into the incidence, patient-related risk factors, endoscopic treatment, and in-hospital mortality in a sizeable AVH collective in Germany. These data might help improve risk stratification and treatment strategies for AVH patients in the future.